Process optimization of vacuum-fried Philippine sweet potato (Ipomoea batatas L.) chips - De Guzman, Edward Peter B.; Luna, Myrna Benita Z. (Quezon City University of the Philippines Diliman, 2024)
The study aimed to optimize the process parameters of vacuum frying Philippine sweet potato (PSP) chips using response surface methodology (RSM). Specifically, the study: (a) evaluated the effects of frying time (Ft), frying temperature (FT), and loading capacity (LC) on the consumer acceptability, moisture content (%MC), water activity (aw), and change in color value (ΔE) of vacuum-fried PSP chips using central composite rotatable design (CCRD); and (b) established the optimum process parameters for vacuum frying of PSP chips using the validated optimization models. It was determined that FT and LC generally had a significant (p<0.05) effect on the consumer acceptability, %MC, aw, and ΔE of vacuum-fried PSP chips. The optimized process parameters for vacuum-fried PSP chips were found to be 7-11.04 min Ft, 90-91.22°C FT, and 27.03-30% LC using the Department of Science and Technology (DOST)-High Impact Technology Solutions (HITS) vacuum fryer. Validation studies showed that the established statistical models were accurate in predicting the responses for the study. It is recommended to investigate the effects Ft, FT, and LC on other response variables such as oil content, total carotenoid levels, and texture. Future studies are also encouraged to evaluate alternative pre-treatment methods and to test for rancidity associated with the number of vacuum frying cycles as an indicator of shelf life.
In partial fulfillment for the Degree of Bachelor of Science in Food Techonology
Thesis
Keywords: Sweet potatoes; Food -- Effect of heat on; Processed foods -- Philippines; Process optimization; Vacuum frying; Sweet potato chips; Response surface methodology